Pharmaceutical Statistics. V.25 - Bolton, Sanford (USA : New York, 1984)
This book would stimualate the introduction of formal courses in statistics within college of pharmacy at both the undergraduate and graduate levels.
Keywords: Pharmacy; Pharmacy -- Statistical methods